2002
DOI: 10.1056/nejmoa012052
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion Involving the Connexin 30 Gene in Nonsyndromic Hearing Impairment

Abstract: A 342-kb deletion in GJB6 is the second most frequent mutation causing prelingual deafness in the Spanish population. Our data suggest that mutations in the complex locus DFNB1, which contains two genes (GJB2 and GJB6), can result in a monogenic or a digenic pattern of inheritance of prelingual deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
466
1
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(502 citation statements)
references
References 29 publications
22
466
1
13
Order By: Relevance
“…The most frequent causative gene for nonsyndromatic SNHL is GJB2 ( CX26 ) (Smith et al, 2014 2014). Although less frequent, mutations in GJB6 ( CX30 ) (Grifa et al, 1999; del Castillo et al, 2002) and GJA1 (CX43) (Liu et al, 2001; Hong et al, 2010) have also been linked to SNHL. These gap junction proteins are thought to play a role in maintaining cochlear ion homeostasis and the endocochlear potential, as shown in Gjb6 ‐deficient mice (Teubner et al, 2003), by passively recycling K + ions back to the stria vascularis.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent causative gene for nonsyndromatic SNHL is GJB2 ( CX26 ) (Smith et al, 2014 2014). Although less frequent, mutations in GJB6 ( CX30 ) (Grifa et al, 1999; del Castillo et al, 2002) and GJA1 (CX43) (Liu et al, 2001; Hong et al, 2010) have also been linked to SNHL. These gap junction proteins are thought to play a role in maintaining cochlear ion homeostasis and the endocochlear potential, as shown in Gjb6 ‐deficient mice (Teubner et al, 2003), by passively recycling K + ions back to the stria vascularis.…”
Section: Discussionmentioning
confidence: 99%
“…and GJB6 present at this locus encoding the proteins connexin 26 (Cx26) and connexin 30 (Cx30) [18][19][20]. Some 111 mutations associated with NSHI have been described in GJB2, of which 92 have an autosomal recessive (AR) mode of inheritance, nine are inherited as autosomal dominant (AD) mutations, and 10 others have no clearly defined pattern of transmission [17].…”
Section: Introductionmentioning
confidence: 99%
“…This deletion was the second most frequent connexin mutation reported for NSHI in Spain, France, Israel, Great Britain and Brazil [20,25]. Individuals who are either homozygous for del(GJB6-D13S1830) or compound heterozygotes of del(GJB6-D13S1830) and a mutant allele of GJB2 develop NSHI, resulting in profound to severe HI [26].…”
Section: Introductionmentioning
confidence: 99%
“…The 309 kb deletion involving GJB6 [Lerer et al, 2001;Pallares-Ruiz et al, 2002;del Castillo et al, 2002] was observed only once, in a patient of unknown ethnicity who is heterozygous for a p.Gln57X (p.Q57X) mutation in GJB2 (data not shown). In this patient, detection of heterozygous mutations in GJB2 and GJB6 supports an etiologic diagnosis of DFNB1-associated hereditary hearing loss.…”
mentioning
confidence: 95%
“…It is likely that founder effects, population stratification, and assortative mating at least partially explain the variable frequency of these deletions in different populations [Lerer et al, 2001;Pallares-Ruiz et al, 2002;del Castillo et al, 2002;Fitzgerald et al, 2004;Gualandi et al, 2004;Roux et al, 2004;Dalamon et al, 2005;Del Castillo et al, 2005;Seeman et al, 2005].…”
mentioning
confidence: 99%